Cultivar-by-environment interactions shape strawberry fruit quality: A multi-omics approach across European climates - Pacheco-Ruiz, Patricia; Senger, Elisa; Pott, Delphine M.; Ziegler, Freya M.R.; Jiménez, Lidia; Sønsteby, Anita; Krüger, Erika; Masny, Agnieszka; Mott, Daniela; Petit, Aurélie; Savini, Gianluca; Usadel, Björn; et al. (Elsevier, 2026)
Flavour inconsistency in Fragaria x ananassa remains a challenge, largely due to historical breeding focused on yield over sensory traits. Flavour results from organoleptic and bioactive compounds shaped by cultivar (G), environment (E) and their interaction (GxE). Four strawberry cultivars (Clery, Frida, Gariguette, Sonata) were evaluated across five European environments employing an integrative approach combining metabolomics and transcriptomics. This approach revealed elevated temperatures accelerate the start of the harvest season and shorten fruit development duration. GxE interactions critically influenced flavour compounds accumulation, indicating cooler temperatures during fruit development favor the accumulation of sugars and ɣ-decalactone. Integrative analysis identified cultivar-specific and environmentally stable transcriptional patterns, including promising candidate genes involved in the biosynthesis and degradation of flavour relevant compounds, and revealing starting points for strawberry flavour improvement and stabilization. Our findings highlight the central role of GxE interactions in shaping strawberry flavour profile and emphasize the need for multi-environment trials to support resilient flavour enhancement in future breeding programs.
Keywords: Fresas - Variedades; Cultivos - Mejora; Frutas - Sabor y olor; Strawberry flavour; Cultivar-by-environment interactions; Multi-omics approach; Metabolomics; Transcriptomics; Multivariate analysis; Predictive modelling